The Analysis of Wealth Structure and Firm Size on Firm Value of Food and Beverage - Ilyas Lamuda; Maysyar Yusuf; Meimoon Ibrahim (Atestasi : Jurnal Ilmiah Akuntansi, 2020)
This study aims to analyze the effect of wealth structure and company size on company value in the food and beverage sector to maximize the wealth structure and company size to support firm value. This research is a causal associative study with multiple linear regression analysis methods. The determination of the sample in the study used data from companies in the food and beverage sector listed on the IDX for the 2015-2019 period with a purposive sampling technique. The results show that the wealth structure has a positive and significant effect on firm value, this is because the food and beverage sector companies are a type of company that has a high earning value of productive assets, so they tend to seek internal funding, this gives a signal to investors that the company will maximize company profits for them by not adding to the financing burden of the financial burden of debt later, the characteristics of the food and beverage industry that require large capital and operational experience cause company size to have a positive and significant effect on firm value.